Impact of Reference Mismatch on Procedure Outcomes of Percutaneous Coronary Intervention. (May 2023) - Phan, Quang Tan; Nguyen, Hieu Lan; Lee, Wang Soo; Won, Ho Youn; Cho, Iksung; Shin, Seung Yong; Hong, Joon Hwa; Lee, Jin Bae; Kim, Sang Wook
A significant mismatch between proximal and distal reference lumen diameters of the target lesion may pose challenges during percutaneous coronary intervention (PCI) and therefore influence the outcomes. We investigated total 1706 lesions underwent IVUS guided percutaneous coronary intervention, that were divided into 2 groups, including 411 lesions in Mismatch group and 1295 lesions in Non-Mismatch group. After propensity score matching, 397 lesions in each group were selected for final data set. The analysis showed that Mismatch group PCI required more frequently use of post-stenting optimization (79.6% vs 53.9%, P < .001) using higher max pressure (19.5 ± 3.9 vs 16.7 ± 3.7 atm, P < .001). Besides, Mismatch group also encountered more PCI major complications (7.8% vs 4.0%, P = .024) and lower procedure success rate (91.4% vs 95.5%, P = .022). On final angiogram, Mismatch group had smaller minimum lumen diameter (2.62 ± .45 vs 2.90 ± .57 mm, P < .001) and lower angiographic success rate (93.2% vs 96.7%, P = .023). On final IVUS, Mismatch group had higher rate of incomplete stent apposition and stent edge dissection (6.3% vs 3.0%, P = .029 and 2.5% vs .5%, P = .021, respectively). In conclusion, reference mismatch posed significant challenging during PCI that led to unfavorable procedural outcomes. These impacts may translate into long-term clinical implications that need to be addressed in future studies.